2019
DOI: 10.1002/eji.201948254
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin‐1 promotes NLRP3 activation during apoptosis but is dispensable for canonical or noncanonical inflammasome activation

Abstract: Inflammasomes are multimeric protein complex that assemble in the cytosol upon microbial infection or cellular stress. Upon activation, inflammasomes drive the maturation of proinflammatory cytokines, IL-1β and IL-18, and also activate the pore-forming protein, gasdermin D to initiate a form of lytic cell death known as "pyroptosis". Pannexin-1 is channel-forming glycoprotein that promotes membrane permeability and ATP release during apoptosis; and was implicated in canonical NLRP3 or noncanonical inflammasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Cleavage of pannexin‐1 by caspase‐3 and caspase‐7 relieves its auto‐inhibitory domain, allowing pannexin‐1 channel activity, membrane permeability, potassium efflux, and NLRP3 inflammasome assembly. In support of this, blockade of pannexin‐1 channel activity but not pannexin‐1 cleavage using small molecule inhibitors abrogated NLPR3 activation in apoptotic cells 79 . Interestingly, under conditions of intrinsic apoptosis, caspase‐8 appears to be equally important as the NLRP3 inflammasome in promoting IL‐1β maturation.…”
Section: Cross Talkmentioning
confidence: 80%
See 1 more Smart Citation
“…Cleavage of pannexin‐1 by caspase‐3 and caspase‐7 relieves its auto‐inhibitory domain, allowing pannexin‐1 channel activity, membrane permeability, potassium efflux, and NLRP3 inflammasome assembly. In support of this, blockade of pannexin‐1 channel activity but not pannexin‐1 cleavage using small molecule inhibitors abrogated NLPR3 activation in apoptotic cells 79 . Interestingly, under conditions of intrinsic apoptosis, caspase‐8 appears to be equally important as the NLRP3 inflammasome in promoting IL‐1β maturation.…”
Section: Cross Talkmentioning
confidence: 80%
“…In addition, recent studies have also uncovered additional mechanisms by which apoptotic cell death drives host defense. First, two studies demonstrated that apoptotic caspase‐8 directly cleaves GSDMD to drive pyroptosis during Yersinia infection 76,77 ; second, caspase‐8 activation has also been observed to direct inflammasome assembly 76,78‐81 although the mechanisms by which this occurs is still debated and is discussed in detail in the later paragraphs.…”
Section: Programmed Cell Death During Bacterial Infectionmentioning
confidence: 99%
“…Proteolytic cleavage of pannexin-1 by active caspase-11 or caspase-4 mediates ATP release, which activates the ATP-gated P2X7 channel, and promotes ion flux [71,[123][124][125]. However, this mechanism has recently been questioned and attributed to NLRP3 activation during apoptosis, but not pyroptosis [126]. In addition, activation of ROS and transient receptor potential channel 1 (TRPC1) may also be involved [127,128].…”
Section: Inflammasome Assemblymentioning
confidence: 99%
“…Although apoptosis was traditionally considered an immunologically silent form of cell death, an increasing number of studies documented that apoptotic caspase‐8 promotes assembly of the NLRP3 inflammasome (Vince et al , ; Lawlor et al , , ; Wicki et al , ; Chen et al , ,b). The existence of this signalling axis was first demonstrated by Vince and colleagues, who reported that loss of IAPs sensitised macrophages and dendritic cells to caspase‐8‐dependent cell death and NLRP3 activation upon TNF or TLR ligation (Vince et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we demonstrate that caspase‐8‐dependent NLRP3 activation requires the channel‐forming transmembrane glycoprotein, pannexin‐1. For this, caspase‐8 promotes downstream executor caspase‐3/7 activation, which cleave and activate pannexin‐1 channel activity, membrane permeability and NLRP3 inflammasome activation (Fig ; Chen et al , ,b). Further support for the importance of pannexin‐1 in driving NLRP3 activation during apoptosis comes from the fact that caspase‐3/7 and pannexin‐1 are also required also for NLRP3 activation upon caspase‐9‐dependent intrinsic apoptosis, which unlike caspase‐8, does not have the ability to cleave GSDMD (Vince et al , ; Chen et al , ,b).…”
Section: Introductionmentioning
confidence: 99%